3(x+5)+2=3(x-4)

Simple and best practice solution for 3(x+5)+2=3(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+5)+2=3(x-4) equation:



3(x+5)+2=3(x-4)
We move all terms to the left:
3(x+5)+2-(3(x-4))=0
We multiply parentheses
3x-(3(x-4))+15+2=0
We calculate terms in parentheses: -(3(x-4)), so:
3(x-4)
We multiply parentheses
3x-12
Back to the equation:
-(3x-12)
We add all the numbers together, and all the variables
3x-(3x-12)+17=0
We get rid of parentheses
3x-3x+12+17=0
We add all the numbers together, and all the variables
29!=0
There is no solution for this equation

See similar equations:

| 8s+43=5s+49 | | .11x/2=10x-9 | | 2x+45=x+81 | | 10+25b=-28 | | .5×n=3 | | 2c=4c-4 | | 11a+9(a+6)=6(11a+9 | | (1/9)^x-3=59049 | | 8x^2+7x-28=0 | | 4w+13=13w-68 | | -2-48-6x-5)=-(-x-2)-x | | 210-2.5x=184-1.5x | | (5x+25)+(3x+19)=180 | | x+4=4x=2 | | x+6=5x=-1 | | 2x+x+10+3x-4=180 | | 14x+7=2x+13 | | 4x0.2=1x4 | | 6+5(-3x-9)=4(-x-4)-2x | | n-5=-8(6+5n | | 3x+3-4=35 | | 50x+40=80x+30 | | (7/3x)+(1/3x)=1+(5/3x) | | 16a-60=12a | | .75r+3=r+1 | | x+4=6x+2 | | 4x+19=7x-13 | | 17s=16s+4 | | 5c+2c+4=25 | | 9x+10=7+32 | | -5(4x-2)-1=3(5x-9)+6x | | (2x-4)=(96-3x) |

Equations solver categories